Trauma informed interventions to reduce seclusion, restraint and restrictive practices amongst staff caring for children and adolescents with challenging behaviours : a systematic review - Peter Kelly and Mohamad M. Saab and Emma J. Hurley and Sinéad Heffernan and John Goodwin and Zamzaliza A. Mulud and Maria O Malley and James O Mahony and Margaret Curtin and Gunter Groen and Svetla Ivanova and Astrid Jörns-Presentati and Joonas Korhonen and Kostadin Kostadinov and Mari Lahti and Valentina Lalova and Gergana Petrova and Aine O Donovan (Journal of child & adolescent trauma, 2023)
Engaging with children and adolescents in mental health settings who are exhibiting behaviours that challenge can often result in the use of seclusion, restraint and coercive practices. It is recognised that more therapeutic ways to engage this population are needed, adopting trauma informed interventions may provide a solution. The aim of this systematic review is to synthesize the evidence in relation to the effect of trauma-informed interventions on coercive practices in child and adolescent residential settings. The review is guided by elements of the Cochrane Handbook for Systematic Reviews of Interventions and reported using the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) checklist. Results were synthesized and reported narratively. Nine studies met the eligibility criteria for this review. There was a lack of homogeneity amongst the studies. The trauma-informed interventions used were typically multi-faceted, underpinned by a variety of approaches and sought to bring about changes to clinical practice. Most studies (n = 8) reported significant reductions in the use of restrictive practices following the implementation of a trauma informed approach. The use of a trauma-informed approach, underpinned by an organisational change or implementation strategy, have the potential to reduce coercive practices with children and adolescents. However, the included interventions were insufficiently described to draw strong conclusions.
Keywords: Adolescents; Children; Coercive practice; Interventions; Trauma informed care; Violence and aggression